Application of high technology coverage for prevention of pressure injury: case series (Research, Society and Development, 2023)
Objectives: To describe the use of high technology coverage (transparent polyurethane film) in the prevention of pressure injuries and to identify the presence of possible pressure injuries during and after using the proposed coverage. Methodology: Descriptive, prospective study of the case series type, with the involvement of patients hospitalized in the sectors of internal medicine and intensive care units of a university hospital in the city of Rio de Janeiro with 10 participants who received the application of preventive technology for prevention of pressure injury. Data collection was carried out between October and November 2022. Results: Ten patients were included and evaluated, six from the medical clinic and four from the ICU. After application of the coverage, the pre-established intervals for reassessment were 24, 48 and 72 hours, in all patients it was possible to observe difficulty in applying the coverage, during the research the minimum time of permanence of the coverage was 24 hours and a maximum of 72 hours in both application regions. The average intervention time was 64 hours for the elbows and 55 hours for the heels. During the period, only 03 patients were able to keep the film in the application sites for the time proposed in the study. Conclusion: Although there was no break in the integrity of the skin in any of the research participants after 24, 48 or 72 hours of application of the intervention, it is not possible to state that it is related to the installed technology. Carrying out preventive measures associated with the use of technology can be beneficial for the prevention of pressure injuries.